Respiratory function and symptoms in young preterm children in the contemporary era - Verheggen, M.; Wilson, A.; Pillow, J.; Stick, S.; Hall, Graham (Wiley-Liss, Inc, 2016)
Objective: To determine the relationships between respiratory symptoms, lung function, and neonatal events in young preterm children. Methods: Preterm children (<32 w gestation), classified as bronchopulmonary dysplasia (BPD) or non-BPD, and healthy term controls were studied. Lung function was measured by forced oscillation technique (respiratory resistance [Rrs] and reactance [Xrs]) and spirometry. Respiratory symptom questionnaires were administered. Results: One hundred and fifty children (74 BPD, 44 non-BPD, 32 controls) 4–8 years were studied. Lung function (median Z-score [10,90th centile]) was significantly impaired in preterm children compared to controls for FVC (0.00 [-1.18, 1.76], 0.69 [-0.17,1.86]), FEV1 (-0.44 [-1.94, 1.11], 0.49 [-0.83, 2.51]), Xrs (-1.26 [-3.31, 0.11], -0.11 [-0.97, 0.73]), and Rrs (0.55 [-0.48, 1.82], 0.28 [-0.99, 0.96]). Only Xrs differed between the BPD and non-BPD (-1.51 [-3.59, -0.41], -0.89 [-2.64, 0.52]). The prevalence of recent respiratory symptoms (range: 32–36%) did not differ between BPD and non-BPD children. Supplemental O2 in hospital was positively associated with worsening Xrs and FEV1. Conclusion: Preterm children have worse lung function than healthy controls. Only respiratory reactance differentiated between preterm children with and without BPD and was influenced by days of O2 in hospital. Pediatr Pulmonol. 2016;51:1347–1355.